The management team handbook five key strategies for maximizing group performance - McIntyre, Marie G. 1947- (The Jossey-Bass business and management series, 1998)
Based on research involving more than seventy management teams and on the author's own extensive team-consulting experience, this book outlines five success factors proven to optimize the performance of management teams in business, government, and nonprofit organizations. Including a flexible team model, assessment survey, compelling case studies, and other results-oriented tools, The Management Team Handbook is a one-of-a-kind guide to creating and maintaining the most dynamic management teams possible.